Media normalization for marketing swimming schools for people with special needs - Mohamed Taher Shousha, Nadia (sports creativity, 2025)
The media is a vital necessity in any modern society. The advancement of science and knowledge, and the application of scientific theories in all aspects of human life, have made the media increasingly important and essential as society becomes more complex due to technological progress. A society cannot truly prosper unless its members are in harmony and its public adapts to its civil and governmental organizations. The media is but one of the important means by which this understanding and harmony are achieved through shared experiences, perspectives, and emotions. In essence, media outlets are tools for raising awareness and disseminating information, regardless of their diverse forms and circumstances. They all fall under the umbrella of what we can call the cultural media for ideas and experiences. Whether primitive or sophisticated, this medium is the primary driver of dissemination and exposure. Without it, societies would close their doors, with each group living in isolation. Media also plays a fundamental role in shaping societies, in the dissemination and development of their production, and in the transfer of science and knowledge to others. Furthermore, sports, as a characteristic of small communities that involve specific physical and intellectual activities among their members, rely heavily on these media for the rapid transmission of information. Developing and improving its performance level from the small community scale to the large community scale. The media in any society is responsible for formulating, publishing, and distributing news, information, ideas, and opinions. Consequently, it becomes one of the most effective means in any society for changing values ​​and attitudes, promoting and reinforcing positive behavior, and marginalizing negative behavior within the same society. Therefore, governments, governmental and private institutions, civil society organizations, associations, and bodies related to society and its segments rely on mass media (radio, television, cinema, press, newspapers, magazines) to reach the target audience and achieve the desired goals. The importance of sports media is evident in its ability to deliver information and data in the form of messages to a large and diverse audience with varying orientations and differing public opinions on a particular issue or problem. It strongly influences the public and has the ability to change behavioral patterns, whether by encouraging good behavior or discouraging bad behavior. Sports media is considered one of the main foundations of any media outlet, as sports have become an important social and cultural phenomenon in modern societies. Consequently, sports media worldwide has received great attention and ample care from all media outlets. The media has several concepts and definitions, including: It is “the communication between the sender (journalist) and the receiver (public) through a media outlet that transmits the media message from one party to another.” Zaidan Abdel Baqi defines it as “providing the public with the greatest amount of correct information or established and clear facts.” It is “publishing information after collecting and selecting it.” It is “persuasion through information, facts, and figures. It is the objective expression of the public’s mentality, spirit, inclinations, and directions at the same time. It is not a subjective expression on the part of the media.”